2016
DOI: 10.1073/pnas.1522306113
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying the social enhancement of vocal learning in songbirds

Abstract: Social processes profoundly influence speech and language acquisition. Despite the importance of social influences, little is known about how social interactions modulate vocal learning. Like humans, songbirds learn their vocalizations during development, and they provide an excellent opportunity to reveal mechanisms of social influences on vocal learning. Using yoked experimental designs, we demonstrate that social interactions with adult tutors for as little as 1 d significantly enhanced vocal learning. Soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
181
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(201 citation statements)
references
References 49 publications
10
181
3
Order By: Relevance
“…But errors in song imitation are not entirely random: the accuracy of song imitation varies with environmental (Nowicki et al, 2002) and social (Chen et al, 2016;Tchernichovski and Nottebohm, 1998) conditions. Furthermore, there is evidence that the accuracy of song imitation may change adaptively -i.e.…”
Section: How Song Learning Sustains Polymorphic Dialectsmentioning
confidence: 99%
See 1 more Smart Citation
“…But errors in song imitation are not entirely random: the accuracy of song imitation varies with environmental (Nowicki et al, 2002) and social (Chen et al, 2016;Tchernichovski and Nottebohm, 1998) conditions. Furthermore, there is evidence that the accuracy of song imitation may change adaptively -i.e.…”
Section: How Song Learning Sustains Polymorphic Dialectsmentioning
confidence: 99%
“…In the other siblings, song imitation is partially inhibited, resulting in divergence (Tchernichovski and Nottebohm, 1998). This is not due to lack of opportunity to learn from a busy tutor: a recent study showed that the rate at which tutors produced song is inversely related to pupil attention and to song learning (Chen et al, 2016). Therefore, divergence appears to be an active process.…”
Section: How Song Learning Sustains Polymorphic Dialectsmentioning
confidence: 99%
“…Similarly, vocal learning (especially imitation and mimicry) is thought to be a key precursor of high-order vocal communication systems, such as language (Jarvis, 2006a,b;Lipkind et al, 2013), and only a subset of species exhibits vocal learning: parrots, songbirds, humming birds, humans, bats, dolphins, whales, sea lions, and elephants (Reiss and McCowan, 1993;Tchernichovski et al, 2001;Poole et al, 2005;Pepperberg, 2010;King and Janik, 2013;Chen et al, 2016). More recently, Watson et al (2015) have added chimpanzees to the list.…”
Section: Comparative Analysis Of Human and Animal Vocalizationmentioning
confidence: 99%
“…Increases in signal production suggest the signaller has control over its signalling in response to audience characteristics. The second reason audience effects are important is because some examples suggest that signallers are aware of receivers’ perceptual states, and can modify their signal use accordingly (Chen et al, 2016; Tomasello & Zuberbühler, 2002; Townsend et al, 2016; Zuberbühler, 2008). For example, when male Thomas langurs, Presbytis thomasi , detect predator stimuli, they continue to produce alarm calls until all members of their group respond with a countercall (Wich & de Vries, 2006).…”
mentioning
confidence: 99%
“…These types of signal modifications may also be more taxonomically widespread. Recent evidence from birds shows that adult zebra finch, Taeniopygia guttata , tutors that direct songs to young male learners (pupils) include more repeated elements and longer spacing between song elements (Chen et al, 2016). These authors also found that tutors altered the fine structure of their songs by modifying mean frequency, spectral entropy and goodness of pitch in ways that appear to increase pupil attention and may improve pupil song learning.…”
mentioning
confidence: 99%